2024
DOI: 10.1021/acs.orglett.4c00292
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access to Chiral Spiro[2.3] Lactams: Stereoselective Hydroborylation and Hydrosilylation and Remote Control of Axial Chirality by Copper-Catalyzed Desymmetrization of Spirocyclopropenes

Changsheng Zhou,
Yixin Liang,
Ying Li
et al.

Abstract: Chiral spirocyclopropyl β-lactams are common motifs in bioactive compounds and pharmaceuticals. Here we disclose a diastereoselective and enantioselective hydroborylation and hydrosilylation of spirocyclopropenes, via a Cu-catalyzed desymmetrization strategy, for the rapid preparation of enantio-enriched spirocyclopropyl β-lactams. The efficient desymmetrization strategy allows the remote control of axial chirality, offering the borylated and silylated products bearing central, spiro, and axial chirality. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In 2022, Lin et al reported an atroposelective desymmetric cycloaddition of N -arylmaleimides using phosphine as the catalyst for the convenient construction of two central chiralites and a remote C Ar –N axial chirality . Very recently, Zhang et al presented a Cu-catalyzed desymmetrization of spirocyclopropenes for the access to central, spiro, and axial chiralities in one step . Despite this progress, the existing methods are limited to cyclic alkenes and the generation of C Ar –N axial chirality.…”
mentioning
confidence: 99%
“…In 2022, Lin et al reported an atroposelective desymmetric cycloaddition of N -arylmaleimides using phosphine as the catalyst for the convenient construction of two central chiralites and a remote C Ar –N axial chirality . Very recently, Zhang et al presented a Cu-catalyzed desymmetrization of spirocyclopropenes for the access to central, spiro, and axial chiralities in one step . Despite this progress, the existing methods are limited to cyclic alkenes and the generation of C Ar –N axial chirality.…”
mentioning
confidence: 99%